India's power elite: class, caste and a cultural revolution - Baru, Sanjaya (Gurugram Viking, 2021)
India's Power Elite is a study of the nature of power and elitism in postcolonial India. Its point of departure is the political transition under way in twenty-first-century India, with the marginalization of the Congress Party and the staging of a cultural revolution symbolized by the rise of Hindu majoritarianism.
Keywords: Politics and government; Social classes